Caractéristiques temporelles et endocriniennes de la puberté et du cycle oestral chez la chèvre locale - Aïssata Wereme (Biotechnologie, Agronomie, Société et Environnement, 1998)
Temporal and hormonal characteristics of puberty and oestrous cycle in a local goat breed (Mossi) of Burkina Faso.Age at puberty, duration of sequences in oestrous cycle and timespan of heat, and sex hormone (FSH, LH and E17Beta) levels in blood plasma were studied in local Mossi goats. The study was designed to provide the tools for an improved mating management of this breed in its natural eco-climatic environment. For heat detection, harnassed bucks without markers were put into female paddocks three times a day, and were continuously observed by a trained technicien. Sex hormones in blood plasma were analysed using radioimmunoassay (RIA). There were Ovide individuel variations in plasma FSH and E-17Beta levels. Apparent age at puberty (AAP) was observed around 7.5 months, but actuel AAP as shown by the first ovulation in reproductive life was six months. Mean duration of estrus cycle was 21 ± 6 days, characterized by two main sequences: a follicular phase lasting about three days, followed by an 18 day luteal phase. Visible signs of estrus lasted 20 ± 2 hours. Preovulatory LH peak surge (50 to 302 ng/ml blood plasma depending on animais) occurred between the 14th and the 22nd hour following the beginning of heat signs. This indicates that the best time for artificial or natural insemination of Mossi goat does fall between the 26th and the 34th hour after the first signs of heat